Diagnostic value of cerebrospinal fluid CXCL13 for acute Lyme neuroborreliosis. A systematic review and meta-analysis. (December 2018) - Rupprecht, T.A.; Manz, K.M.; Fingerle, V.; Lechner, C.; Klein, M.; Pfirrmann, M.; Koedel, U.
Abstract: Objectives: The utility of cerebrospinal fluid (CSF) CXCL13 for diagnosis of acute Lyme neuroborreliosis (LNB) has been debated and the test is not yet routinely performed. This study's aim was to evaluate its overall diagnostic accuracy through meta-analysis. Methods: Electronic searches in PubMed MEDLINE and Web of Science were performed to identify relevant articles published before January 2018. A summary receiver operating characteristic curve and an optimal cut-off were estimated modelling multiple cut-offs. Publication bias was evaluated using a funnel plot and the associated regression test. Results: A total of 18 studies involving 618 individuals with acute LNB and 2326 individuals with other neurological disorders meeting the eligibility criteria were identified. The pooled sensitivity for CSF CXCL13 was 89% (95% CI 85%–93%) and the pooled specificity was 96% (95% CI 92%–98%), using the identified optimal cut-off value of 162 pg/mL. There was marked heterogeneity between studies, caused by differences in the designs of the study populations and age distribution. The optimal cut-off in the seven studies with a cross-sectional design was 91 pg/mL (sensitivity 96%, 95% CI 92%–98%; specificity 94%, 95% CI 86%–97%) and in the 11 case–control studies it was 164 pg/mL (sensitivity 85%, 95% CI 78%–91%; specificity 95%, 95% CI 90%–98%). CSF CXCL13 values above the optimal cut-off level (determined in this meta-analysis) were also detectable in some other central nervous system disorders, namely neurosyphilis and central nervous system lymphoma. Conclusions: Our meta-analysis shows that CSF CXCL13 has the potential to become a useful adjunct in the diagnosis of acute LNB.